Biometric aspects of fruits and diaspores from Mauritia flexuosa from the brazilian Cerrado - Campos, Thiago Souza [UNESP]; de Souza, Antonio Maricélio Borges [UNESP]; Vieira, Guilherme Rodrigues [UNESP]; Pivetta, Kathia Fernandes Lopes [UNESP] (Universidade Federal de Santa Maria, 2023)
The buriti palm (Mauritia flexuosa L. f.) serves as a raw material for the food, pharmaceutical and biotechnological industries but it has a low germination rate and seed viability, which are directly related to the morphological characteristics of the fruits and seeds. Biometric characterization provides information necessary for the differentiation, characterization of ecological and genetic aspects of different species and populations of the same group, and can help in the conservation and propagation of species. The current work performed the biometric characterization of fruits and diaspores of Mauritia flexuosa from a cultivation environment in the Brazilian Cerrado. 100 fruits were randomly sampled, which were measured in length, width, thickness, individual weight, diaspore length, diaspore width, diaspore thickness and individual diaspore weight. Fruits were classified as red (Hue 10 R 4/8) and yellow-orange diaspores (Hue 7.5 YR 8/8). Data for each characteristic were submitted to descriptive statistical analysis. The fruits varied by 6.56% in length, 4.38% in width and 4.26% in thickness while the diaspores varied by 8.17% in length, 9.29% in width and 9.62% in thickness. The variables fruit weight and diaspore weight showed the greatest variations, 12.12% and 23.86%, respectively. There was a positive correlation between width and thickness (0.90). The small variation in biometric dimensions indicates that the species has little variability.
Aspectos biométricos dos frutos e diásporos de Mauritia flexuosa provenientes do Cerrado brasileiro
Keywords: Arecaceae; Buriti; Conservation; Morphometry